2021
DOI: 10.1371/journal.ppat.1009404
|View full text |Cite|
|
Sign up to set email alerts
|

Robust CAR-T memory formation and function via hematopoietic stem cell delivery

Abstract: Due to the durability and persistence of reservoirs of HIV-1-infected cells, combination antiretroviral therapy (ART) is insufficient in eradicating infection. Achieving HIV-1 cure or sustained remission without ART treatment will require the enhanced and persistent effective antiviral immune responses. Chimeric Antigen Receptor (CAR) T-cells have emerged as a powerful immunotherapy and show promise in treating HIV-1 infection. Persistence, trafficking, and maintenance of function remain to be a challenge in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…In comparison with UTD cells, there was no significant difference among the CD62L expression of 3B, 3BE and 3BE/TCR-CAR-T cells (figure 5A). The data showed that the CD62L+ cells in all the groups of anti-HIV CAR-T cells we manufactured were over 60%, which indicated that our CAR-T cells were mainly composed of naive and central memory cells, a phenotype associated with greater in vivo anti-HIV activity 35,50 (figure 5A). The expression of CD45RA was also tested and the percentages of CD45RA+ cells were lower than 7% in all the anti-HIV CAR-T cells (figure 5A).…”
Section: The Secretion Of E27 and The Deficiency Of Tcr Do Not Impact...mentioning
confidence: 97%
“…In comparison with UTD cells, there was no significant difference among the CD62L expression of 3B, 3BE and 3BE/TCR-CAR-T cells (figure 5A). The data showed that the CD62L+ cells in all the groups of anti-HIV CAR-T cells we manufactured were over 60%, which indicated that our CAR-T cells were mainly composed of naive and central memory cells, a phenotype associated with greater in vivo anti-HIV activity 35,50 (figure 5A). The expression of CD45RA was also tested and the percentages of CD45RA+ cells were lower than 7% in all the anti-HIV CAR-T cells (figure 5A).…”
Section: The Secretion Of E27 and The Deficiency Of Tcr Do Not Impact...mentioning
confidence: 97%
“…CD19-CAR T cell infusion in this model resulted in tumor regression, together with induction of TAM-secreted cytokines and Treg activity, which resembles clinical observations [ 158 ]. A similar BLT-HM model without introduction of oncogene was used to evaluate the antiviral function of HIV-targeted CAR T cells [ 159 ]. Additionally, CARs targeting one, two, or three HIV epitopes were examined in a PBL-HM model, revealing that multi-specific CARs are required for anti-HIV therapy [ 160 ].…”
Section: In Vivo Models For Car T Cell Functional Evaluationmentioning
confidence: 99%
“…This may allow creating a more favorable environment for CAR-T cells and longer CAR-T cell persistence and efficacy [ 97 ]. This may favor CAR-T cells acquisition of memory cell’s function [ 98 , 99 ], which may provide long-term immune recognition of cancer [ 100 ] ( Figure 5 ).…”
Section: Cancer-associated Immune Cell Populationsmentioning
confidence: 99%
“…The interaction of CAR-T cells with immunoregulatory environments has been shown by CAR-T memory formation and function via hematopoietic stem cells (HSC) [ 98 ], which were shown to be common in multiple cancer types and appeared supported by CAF-originated cytokines [ 136 ]. Tumor-associated myelopoiesis was recently demonstrated, and this was shown to generate immune-suppressive myeloid populations [ 164 ].…”
Section: Immune Cell Dynamics and Car-t Anticancer Responsementioning
confidence: 99%